The new insights into cadmium sensing - Chmielowska-Bąk, Jagna; Gzyl, Jarosław; Rucińska-Sobkowiak, Renata; Arasimowicz-Jelonek, Magdalena; Deckert, Joanna (Frontiers in Plant Science, 2014)
Cadmium (Cd) is non-essential heavy metal, which in excess, exhibits deleterious effects to the most of the organisms. Mobilization of defense mechanisms against this toxic agent requires rapid activation of signaling pathways. The article presents recent advances in the research concerning cadmium signal transduction in plants. New insights into the involvement of reactive oxygen species, nitric oxide, plant growth regulators and Cd-induced protein modifications are reviewed. Moreover, the role of recently recognized Cd-associated signal elements, including micro RNAs and several cis- and trans- acting elements is discussed.